Development of kano model and quality function development integration to assess customer satisfaction and dissatisfaction of service at local public hospital. - Norshahrizan Nordin (2015)
The intensifying patient complaints on service delivery performance of local public healthcare institution are critical and incrementally raised. New methodologies are needed to address the complexity of patient expectation before the quality of service delivery can be improved. This issue needs to be solved instantly by establishing the service satisfaction model to understand the nature of patient’s expectation towards service delivery. As a result, the developed service satisfaction model has contributed to be inaccurate to understanding of patient’s behavior towards healthcare service. The non-linear assumption should be considered for better accuracy since the non-linear patient’s expectation remains undefined. This thesis aims to develop the non-linear service satisfaction model that assumes patients are not necessarily satisfied or dissatisfied with good or poor service delivery. With that, compliment and compliant assessment is considered, simultaneously. Non-linear service satisfaction instrument called Kano-Q and Kano-SS is developed based on Kano model and Theory of Quality Attributes to define the unexpected, hidden and unspoken patient satisfaction and dissatisfaction into service quality attribute. A new Kano-Q and Kano-SS algorithm for quality attribute assessment is developed based satisfaction impact theories and found instrumentally fit the reliability and validity test. The results were also validated based on standard Kano model procedure before Kano model and Quality Function Deployment (QFD) is integrated for patient attribute and service attribute prioritization. An algorithm of Kano-QFD matrix operation is developed to compose the prioritized complaint and compliment indexes. Finally, the results of prioritized service attributes are mapped to service delivery category to determine the most prioritized service delivery that need to be improved at the first place by healthcare service provider. The results of this study indicate that the new satisfaction model is significantly effective in differentiating Kano dimensions and provides more accurate prioritization of the dimension and attribute compared to the traditional Kano approach. Although the new methodology evaluates the Kano methodology with QFD integration, the methodology is limited to a particular service industry that always encountered high dissatisfaction which expected to compose the Must-be, Attractive and One-dimensional quality attribute by ranking. As a conclusion, the new non-linear Kano-QFD service satisfaction model has been developed, tested and validated with Kano model to facilitate the analysis and decision making for better service delivery improvement. Comparison with other models has shown well agreement in terms of Kano quality attributes satisfaction impact and service gaps in healthcare service. As for future work, the comparison study on linear and non-linear patient expectation based on Kano-QFD integration is essentially recommended.